On-farm Lamb Birth Weight and Growth Performance of Indigenous Sheep Breeds in Burie District, North Western Ethiopia - Abebe, Yenesew (Journal of Agriculture and Environmental Sciences, 2019)
This study was conducted in Burie District in North Western Ethiopia. The objectives of the study were to assess the on-farm birth weight and growth performance of indigenous sheep lambs. Three kebeles were selected for this study in Burie District. From each kebele 20 farmers having 5 or more breeding ewes were selected randomly. This study was conducted for 6 months. Farmers fed their breeding ewes on grazing lands and crop aftermath. The breeding ewes were supplemented with Atella (a residue of local alcoholic beverage) and food leftover. On average, there were 7.6 (SD =2.58) and 8.0 (SD = 3.50) heads of sheep per household at the beginning and at the end of the study, respectively. The birth weight of male lambs (2.6 kg) was greater (p<0.001) than the birth weight of female lambs (2.1 kg). The birth weight of Washera lambs (2.8 kg) was greater than the birth weight of Horro lambs (1.8 kg). There was no difference on the mean growth rate of male and female lambs. In addition, there was no difference on growth rate between Washera and Horro lambs. Generally, Washera lambs were heavier at birth than Horro lambs. There was no difference in body weight and growth rate between the two sheep breed lambs at 112 days of age. The results of this study indicated that Horro lambs had a lower birth weight than Washera lambs, but Horro lambs had similar body weight and growth rate with Washera lambs at 112 days of age when the two sheep breeds are compared within their respective breeding environments. To confirm the current results further studies should be conducted involving more animals and comparing the two breeds within the same environmental conditions.